PREVENTION OF DENTAL CARIES IN PRESCHOOL AGE - Gergana Markova; Rositsa Tsankova-Mihaylova (Peytchinski Publishing, 2023)
Dental caries affects all age groups, but especially children who are of preschool age. The disease is socially significant and affects the quality of life. Various interventions are used to prevent dental caries - water fluoridation, fluoride toothpaste, sugar restriction, antimicrobials, regular preventive examinations and, last but not least, oral hygiene. We have developed a health education program (conversation, discussion, film, practical activity) with the aim of preventing dental caries among children who are at the age of 5. The training was presented by 20 children attending the 'Prolet' kindergarten in the city of Pleven. A discussion was held among the children, a film was shown, proper brushing of the teeth was demonstrated, and they were given the opportunity to practice the technique shown to them. Parents were presented with an information board illustrating dental caries and its consequences; they were given flyers showing possibilities for its prevention. In this report, we show the changes in children's behavior (according to their parents) after the realization of the program. A positive effect of the program conducted among the children was reported. In conclusion, we can say that health education is an important element in the prevention of dental caries.